STRENGTHENING FAMILY CONNECTEDNESS IN FAMILIES WITH CHILDREN WITH BEHAVIOURAL PROBLEMS: KEY EXPERTS’ AND PRACTITIONERS’ EXPERIENCES IN THE IMPLEMENTATION OF PARENTING PROGRAMMES - Danhouse, Merle Heather; Erasmus, Charlene J. (Social Work/Maatskaplike Werk, 2024)
Parenting enhancement contributes to the development of positive child behaviour and strengthening of family connectedness. This qualitative study explores the experiences of 10 experts (social workers, child and youth care workers, and researchers) in the field of parenting through semi-structured interviews to strengthen family connectedness in families with children with behavioural problems (FCBPs). Using Tesch’s qualitative analysis, three main themes emerged: (a) barriers to family connectedness, (b) parenting styles, and (c) parenting programmes in strengthening family connectedness. The findings of the study highlight the barriers experienced by experts and the lack of evidence-based parenting programmes in the strengthening of family connectedness in FCBPs in rural areas in South Africa. The study therefore recommends that practitioners in the field of parenting should receive specialised parenting training on how to strengthen family connectedness in FCBPs.